Holistic Education Perspective of KH. Ahmad Dahlan: Forming Moral Students in the Era of Industrial Revolution 4.0 (Case Study at SDIT Assalam Sanden) - Kurniawan, Ilham; Habibburrahman, Habibburrahman (Al-Ulum: Jurnal Pendidikan Islam, 2025)
Holistic education from the perspective of KH. Ahmad Dahlan is one of the relevant approaches to form a skilled and well-mannered young generation in the era of the industrial revolution 4.0 because it integrates Islamic and intellectual values by emphasizing active learning and developing social awareness. The place where this research was conducted was SDIT Assalam Sanden, with a descriptive qualitative approach as the method used. Meanwhile, data collection techniques in this study include observation, interviews and documentation. The formation of student morals through holistic education from the perspective of KH. Ahmad Dahlan at SDIT Assalam Sanden has been carried out well. The implementation of holistic education includes four stages, namely planning, implementation, control and evaluation.